2012
DOI: 10.1038/ijo.2012.99
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index prior to old age and disability in old age

Abstract: OBJECTIVES: To analyse the relationship between body mass index (BMI) in middle-age and disability status in old-age using data from the Melbourne Collaborative Cohort Study (MCCS). METHODS: A total of 41 514 participants enroled in the MCCS between 1990-1994. Height and weight were measured at baseline and disability, defined as limitations to self-care activities of daily living (ADLs) and self-care plus mobility activities, was identified at follow-up (2003-2007). In all, 6300 participants were o65 years at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…In males, our results were consistent with other studies (2-4, 7, 21-23), which found associations of obesity, higher BMI or higher WC with increased risk of ADL limitation. There are several possible explanations for this association.…”
Section: Discussionsupporting
confidence: 93%
“…In males, our results were consistent with other studies (2-4, 7, 21-23), which found associations of obesity, higher BMI or higher WC with increased risk of ADL limitation. There are several possible explanations for this association.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a recent review and meta-analysis on the association between BMI and dementia showed a positive association between abnormal BMI and dementia when BMI was measured in mid-life, not in late-life 31. Our finding of a threefold increase in the probability of disability associated with obesity is similar to the association found by Backholer et al 8 in a cohort of 6300 Australians aged under 65 at baseline and followed up over 14 years. Backholer et al reported an OR for ADL disability of 2.74 (95% CI 2.10 to 3.58) for women with class 1 obesity (BMI 30–35 kg/m 2 ) and OR of 4.21 (95% CI 3.12 to 5.88) for women with obesity class 2 and above (BMI ≥35 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 87%
“…6 In a large study sample of subjects, a significant relation between BMI assessed at midlife and disability in old age was observed even after taking into account several covariates. 5 After a 26-year follow-up, overweight and obese midlife men showed, respectively, 2.06 and 5.41 higher risk to become frail in old ages. Weight gain from midlife to old age was higher in subjects who became prefrail or frail in older ages.…”
mentioning
confidence: 99%